Evaluating the Steps of Building the Organizational Structure by Supply Chain Performance measurement and productivity: A Case of the General Directorate of Vocational Education - Aymen Hadi Talib; Hind Abdul Ameer Ahmed; Ameer Jawad Kadhim Al-msary (International Journal of Supply Chain Management, 2019)
Abstract- Proper supply chain performance plays a crucial role in the success of the organization. Therefore, it is essential to use an appropriate supply chain performance assessment system to continuously improve it. The purpose of this research is to analyze supply chain performance according to the operational reference model of supply chain. Organizational structure is one of the fundamental issues and important themes for organizational business as technological developments, increased competition and continuous change are the rudiments of the contemporary business environment. Several questions from the expression of the problem of research provoked the necessity of the study. To identify the reality of the organizational structure in the Directorate General of Vocational Education and the steps needed to be followed are the objectives of this study. The population of the study is selected from a group of departmental managers and various administrative levels of the divisions in the organization are surveyed. The main tool for data collection is questionnaire while only 31 responses are realized from the distribution. A set of statistical methods were used to analyse answers in order to reach final results of the study. The study concluded that effective communication plays an important role between the various administrative levels for the purpose of achieving the objective of the organization. Similarly, the study expresses the importance of preparing detailed lists and clear tasks of the work of the Directorate. The task can be performed efficiently due to possession of human resources with high efficiency and appropriate expertise by the directorate. Lastly, a number of recommendations based on the results of the study are presented to the organizations. The study equally outlined the purpose to involve employees at various administrative levels in the executive levels of the goal setting process and the importance of establishing clear organizational relationship between employees at different administrative levels (Unit, Division and Department).